Neutron yields and effective doses produced by Galactic Cosmic Ray interactions in shielded environments in space. (November 2015) - Heilbronn, Lawrence H.; Borak, Thomas B.; Townsend, Lawrence W.; Tsai, Pi-En; Burnham, Chelsea A.; McBeth, Rafe A.
Abstract: In order to define the ranges of relevant neutron energies for the purposes of measurement and dosimetry in space, we have performed a series of Monte Carlo transport model calculations that predict the neutron field created by Galactic Cosmic Ray interactions inside a variety of simple shielding configurations. These predictions indicate that a significant fraction of the neutron fluence and neutron effective dose lies in the region above 20 MeV up to several hundred MeV. These results are consistent over thicknesses of shielding that range from very thin (2.7 g/cm 2 ) to thick (54 g/cm 2 ), and over both shielding materials considered (aluminum and water). In addition to these results, we have also investigated whether simplified Galactic Cosmic Ray source terms can yield predictions that are equivalent to simulations run with a full GCR source term. We found that a source using a GCR proton and helium spectrum together with a scaled oxygen spectrum yielded nearly identical results to a full GCR spectrum, and that the scaling factor used for the oxygen spectrum was independent of shielding material and thickness. Good results were also obtained using a GCR proton spectrum together with a scaled helium spectrum, with the helium scaling factor also independent of shielding material and thickness. Using a proton spectrum alone was unable to reproduce the full GCR results.